2011
DOI: 10.3389/fpsyg.2011.00092
|View full text |Cite
|
Sign up to set email alerts
|

Can Changes in Eye Movement Scanning Alter the Age-Related Deficit in Recognition Memory?

Abstract: Older adults typically exhibit poorer face recognition compared to younger adults. These recognition differences may be due to underlying age-related changes in eye movement scanning. We examined whether older adults’ recognition could be improved by yoking their eye movements to those of younger adults. Participants studied younger and older faces, under free viewing conditions (bases), through a gaze-contingent moving window (own), or a moving window which replayed the eye movements of a base participant (yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 45 publications
(64 reference statements)
8
29
2
Order By: Relevance
“…Such repetition-related decreases in neural activity (i.e., repetition suppression) have been taken as a proxy for memory formation; thus, visual exploration was related to the development of lasting representations. 96 These findings extended prior eye-tracking research, which showed that an increase in visual exploration predicts later memory 97,98 by suggesting that the underlying mechanism for such memory benefits is an increase in hippocampal activity. The relationship between gaze fixations and hippocampal activity during perceptual processing (encoding) may simply reflect the amount of visual information that is extracted and, subsequently, bound into a memory representation by the hippocampus.…”
Section: Neuroimagingsupporting
confidence: 75%
See 2 more Smart Citations
“…Such repetition-related decreases in neural activity (i.e., repetition suppression) have been taken as a proxy for memory formation; thus, visual exploration was related to the development of lasting representations. 96 These findings extended prior eye-tracking research, which showed that an increase in visual exploration predicts later memory 97,98 by suggesting that the underlying mechanism for such memory benefits is an increase in hippocampal activity. The relationship between gaze fixations and hippocampal activity during perceptual processing (encoding) may simply reflect the amount of visual information that is extracted and, subsequently, bound into a memory representation by the hippocampus.…”
Section: Neuroimagingsupporting
confidence: 75%
“…Such repetition‐related decreases in neural activity (i.e., repetition suppression) have been taken as a proxy for memory formation; thus, visual exploration was related to the development of lasting representations . These findings extended prior eye‐tracking research, which showed that an increase in visual exploration predicts later memory by suggesting that the underlying mechanism for such memory benefits is an increase in hippocampal activity.…”
Section: Neuroimagingsupporting
confidence: 72%
See 1 more Smart Citation
“…Therefore, if alternations of attention allocation directly serve binding, or they are a consequence of processing relational information, fixation patterns may correlate with the number of encoded features or relations. Indeed, for young adults the number of fixations during the study of scenes (Loftus, 1972) or objects (Kafkas and Montaldi, 2011), and the number of eye gaze transitions between the features of a to-be-encoded face (Chan et al, 2011;Sekiguchi, 2011), predict retrieval on a subsequent recognition test. According to the same logic, we hypothesized that during associative encoding of discrete items, eye gaze transitions between the two items are indicative of the generation of relational links between them.…”
Section: Attention Eye Gaze Behavior and Associative Memorymentioning
confidence: 99%
“…Age-related differences in viewing patterns are robust and predict memory performance [72] [12]. The extent to which these viewing changes contribute to memory and hippocampal activity in older adults is unknown.…”
Section: Figurementioning
confidence: 99%